AN EMPIRICAL ANALYSIS OF FACTORS INFLUENCING PERFORMANCE OF SHARIAH MUTUAL FUNDS IN INDONESIA - Marsono, A. Dewantoro; Salim, Ubud; Ratnawati, Kusuma; Aisjah, Siti (Jurnal Aplikasi Manajemen, 2022)
This paper aims to identify the factors that affect the performance of shariah mutual funds. This study uses SEM to test the factors that hypothetically influence mutual fund performance, namely mutual fund manager skills, characteristics, and analyst coverage. This study uses a sample of 45 mutual funds registered with the OJK [financial services authority] for at least three years: equity funds, fixed-income funds, and mixed funds. The results indicate that fund manager skills negatively influence mutual fund performance but not significantly. In addition, the characteristics positively affect the mutual fund performance but are insignificant. Last, analyst coverage is positively influencing the mutual fund performance significantly. The results provide information that would benefit the investors in predicting the performance of shariah mutual funds and the fund managers to improve the performance of their managed funds. Further research will ascertain the inability of market-timing skills and asset allocation strategies to improve mutual fund performance.